2020
DOI: 10.1097/j.pain.0000000000001834
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled trial of desipramine, cognitive behavioral therapy, and active placebo therapy for low back pain

Abstract: This clinical trial evaluated the independent and combined effects of a tricyclic antidepressant (desipramine) and cognitive behavioral therapy (CBT) for chronic back pain relative to an active placebo treatment. Participants (n = 142) were patients experiencing daily chronic back pain at an intensity of ≥4/10 who were randomized to a single-center, double-blind, 12-week, 4-arm, parallel groups controlled clinical trial of (1) low concentration desipramine titrated to reach a serum concentration level of 15 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Maarrawi 2018 (amitriptyline 5 mg/day) 59 Hameroff 1985 (doxepin 300 mg/day) 55 Atkinson 1998 (nortriptyline 100 mg/day) 73 Gould 2020 (desipramine 15-65 ng/mL) 69 Atkinson 2007 (desipramine 5-242 ng/mL) 71 Jenkins 1976 (imipramine 75 mg/day) 47 Urquhart 2018 (amitriptyline 25 mg/day) 70 16 trials. 17 Our findings are in accordance with those from a previous review of drug treatments for chronic low back pain, which found TCAs and SSRIs to be ineffective and SNRIs to be effective, although the effects were small.…”
Section: Tcas (3-13 Weeks)mentioning
confidence: 99%
“…Maarrawi 2018 (amitriptyline 5 mg/day) 59 Hameroff 1985 (doxepin 300 mg/day) 55 Atkinson 1998 (nortriptyline 100 mg/day) 73 Gould 2020 (desipramine 15-65 ng/mL) 69 Atkinson 2007 (desipramine 5-242 ng/mL) 71 Jenkins 1976 (imipramine 75 mg/day) 47 Urquhart 2018 (amitriptyline 25 mg/day) 70 16 trials. 17 Our findings are in accordance with those from a previous review of drug treatments for chronic low back pain, which found TCAs and SSRIs to be ineffective and SNRIs to be effective, although the effects were small.…”
Section: Tcas (3-13 Weeks)mentioning
confidence: 99%
“…All of the 22 studies randomly assigned patients into groups. Random sequence generation was based on computer ( n = 15) [ 23 , 25 , 30 33 , 36 43 ], random number table [ 24 , 27 ] ( n = 2), toss dice [ 26 ] ( n = 1), third office [ 28 , 29 , 44 ] ( n = 3), and unclear randomization method [ 34 ] ( n = 1). Due to the content of CBT intervention, the participants and CBT providers were not blinded in most studies, whereas the outcome accessors were blinded in most studies.…”
Section: Resultsmentioning
confidence: 99%
“…The minimal clinical significance will be considered if the pain severity was reported to be a 30% reduction from baseline [ 57 ]. Ten of the included studies indicated CBT induced a clinically significant reduction in pain intensity or disability level [ 23 , 24 , 28 , 29 , 32 – 34 , 39 , 43 , 44 ], whereas 7 studies reported limited or no clinical effects [ 25 , 30 , 31 , 35 , 38 , 40 , 41 ]. Five studies did not report the clinical significance of CBT [ 26 , 27 , 36 , 37 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary study about m-health-based exercise shows that this method is effective for NCLBP but the effect size is not very high. Relevant trials have suggested that psychotherapies such as cognitive behavioral treatment (CBT) [16,17], mindfulness-based stress reduction (MBSR) [18] and self-compassion training (SCT) [19,20] can be effective treatment options for patients with NCLBP. Among them, self-compassion is a state of mind that treats oneself compassionately in the face of pain and stress.…”
Section: Introductionmentioning
confidence: 99%